Settlement and history in Hellenistic, Roman, and Byzantine Galilee: an archaeological survey of the Eastern Galilee - Leibner, Uzi (Texts and studies in ancient Judaism, 2009)
Uzi Leibner aims to provide the most accurate picture possible of the nature and history of the rural settlement in the Lower Galilee during Hellenistic, Roman and Byzantine periods when this region played an important role in the development of both Judaism and Christianity. In an attempt to draw a historical reconstruction based on systematic data, a test case area in the »heart« of ancient Galilee was chosen for this research. Uzi Leibner used two distinct disciplines: the study of the relevant historical sources and the advanced archaeological field survey. Greek, Latin, Hebrew and Aramaic sources concerning settlements in the region were translated and discussed. Some fifty archaeological sites from the periods under discussion were identified and surveyed. The analysis of the finds enabled the author to draw a detailed portrait of settlement - including periods of construction, abandonment, prosperity and decline in each site and in the region as a whole. This book sheds new light on major historical issues such as the origins of the Galilean Jewry in the Second Temple Period, the First Jewish Revolt and its outcomes, the Jews of Galilee under Christian regime, demography, economy, continuity and decline